"The historical narrative in the novel "Southwest of Troy, Southeast of CarthageBy Ibrahim Al-Koni (مجلة إحالات, 2026)
This scientific article aims to open up the theme of history in the texts of the Libyan novelist Ibrahim Al-Koni, and how to work on it as a fundamental theme for contemporary novelisticnarratives. For this dual approach,history/imagination, we chose the novel (Southwest of Troy,Southeast of Carthage) written by Ibrahim Al-Koni in 2017. This novel is a clear example of drawing inspiration from the historical incident in the novel. Especially since the novelist Ibrahim Al-Koni, in this text, relied on a pivotal historical incident inLibyan history, where a battle took place between the American fleet and the Libyan army led by thePasha, “Youssef Al-Qaramanli.” The latter was able to overcome the American fleet and capture the battleship “Philadelphia”. From this perspective, this article attempts to address how to deal with history (a historical event) as a real, realistic discourse in the novel form as an imaginary discourse. That is, working on two basic factors in this equation, between what is realistic and what is imaginary. Highlighting thenarration style adopted by the author in his fictional text.